The relation of floriculture to ethics and aesthetics - Day, Flora (My University, 1895)
Introduction: The industry of flower growing and improvement has progressed rapidly in recent years. It has reached the state where division of labor has given the culture of a single flower to a specialist, who by hybridizing or by propagating some particular variety wins fame and a fortune.
Citation: Day, Flora. The relation of floriculture to ethics and aesthetics. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Floriculture; Hybridization; Propagating; Theses; Manuscripts (documents)